Evaluation of teachers in basic education schools in Al Dakhiliyah Governorate in the Sultanate of Oman of the extent of their organizational commitment - Al- Harasi, Raya Khalifa Fadel; Al- Hidabi, Dawood Abdulmalek Yahya (Journal of Educational and Psychological Sciences, 2022)
The study aimed at evaluating teachers in basic education schools in Al Dakhiliyah Governorate in the Sultanate of Oman for the extent of their organizational commitment. To achieve the objectives of the study, the researchers used the descriptive analytical survey method. Where a questionnaire was built and applied to a sample of (702) teachers of basic education schools in Al Dakhiliyah Governorate in the Sultanate of Oman. The results of the study showed that the teachers’ evaluation of the extent to which principals of basic education schools in Al Dakhiliyah Governorate in the Sultanate of Oman exercise organizational commitment got an overall average (4.24 out of 5); that is, at a (very high) degree and at the level of the axes; The third axis "Moral commitment" got the highest average (4.50) with a (very high) score, followed by the first axis "Emotional commitment" with an average of (4.18), and the second axis "Continuity commitment" got the lowest value with an average (4.04), both of them with a (high) degree. The results also showed that there are statistically significant differences for the teachers’ ratings according to the gender variable in favor of the female category in emotional commitment and continuity, and the results show that there are statistically significant differences according to the two variables of job experience in the second axis, the continuity commitment and the general average of the axes., and there are no statistically significant differences for the estimates. Teachers according to the educational qualification variable.Based on the results, the researchers presented a set of recommendations and proposals, including inviting the concerned authorities in the Ministry of Education, represented by administrative supervision, to hold intensive courses for school principals to develop the concept of organizational commitment, its content and features, and how to enhance it among workers, and to invest in specialized scientific research in the field of organizational commitment.
Keywords: practice; organizational commitment; basic education; Al Dakhiliyah Governorate; the teachers’ point of view